Dilated cardiomyopathy - guidelines for personalization of care - Antonella Spinelli; Gaetano Marino; Alfredo Macchiusi; Stefania Angela Di Fusco; Carlo Pignalberi; Furio Colivicchi (Monaldi Archives for Chest Disease)
The term dilated cardiomyopathy (DCM) refers to a family of diseases characterized by complex interactions between environment and genetic predisposition. Diagnostic tools such as cardiac magnetic resonance imaging should be systematically implemented in clinical practice to define the etiological cause and undertake a specific treatment. We present the case of a young man with DCM and severe left ventricular dysfunction. The patient has a family history of sudden cardiac death (SCD). He is affected by a psychiatric pathology and has a history of alcohol and drug addiction. Many diagnostic hypotheses have been considered for etiological research. The use of a wearable defibrillator to temporarily protect the patient from SCD risk pending the completion of the diagnostic path to establish DCM etiology and the implementation of optimal medical therapy was considered. However, because of the underlying psychiatric pathology and the possibility of poor adherence to the maintenance of the wearable device, the patients would not have been sufficiently protected. Due to the young age of the patient, it was decided to make a personalized therapeutic choice, and he underwent implantation of a subcutaneous defibrillator.